Shedding Light on Drug-Induced Liver Injury: Activation of T Cells From Drug Naive Human Donors With Tolvaptan and a Hydroxybutyric Acid Metabolite. (20th October 2020) - Hammond, Sean; Gibson, Andrew; Jaruthamsophon, Kanoot; Roth, Sharin; Mosedale, Merrie; Naisbitt, Dean J
Abstract: Exposure to tolvaptan is associated with a significant risk of liver injury in a small fraction of patients with autosomal dominant polycystic kidney disease. The observed delayed onset of liver injury of between 3 and 18 months after commencing tolvaptan treatment, along with rapid recurrence of symptoms following re-challenge is indicative of an adaptive immune attack. This study set out to assess the intrinsic immunogenicity of tolvaptan and pathways of drug-specific T-cell activation using in vitro cell culture platforms. Tolvaptan ( n = 7), as well as oxybutyric (DM-4103, n = 1) and hydroxybutyric acid (DM-4107, n = 18) metabolite-specific T-cell clones were generated from tolvaptan naive healthy donor peripheral blood mononuclear cells. Tolvaptan and DM-4103 T-cell clones could also be activated with DM-4107, whereas T-cell clones originally primed with DM-4107 were highly specific to this compound. A signature cytokine profile (IFN-γ, IL-13, granzyme B, and perforin) for almost all T-cell clones was identified. Mechanistically, compound-specific T-cell clone activation was dependent on the presence of soluble drug and could occur within 4 h of drug exposure, ruling out a classical hapten mechanism. However, antigen processing dependence drug presentation was indicated in many T-cell clones. Collectively these data show that tolvaptan-associated liver injury may be attributable to an adaptive immune attack upon the liver, with tolvaptan- and metabolite-specific T cells identified as candidate effector cells in such etiology.